International lending by commercial banks - Donaldson, T. H. (New York : Wiley, 1979)
The book informatively discusses the major problems and questions that face the manager of an international banking operation. Chapters on lending to companies, country lending, forms of lending, syndicated loans, credit decisions and credit controls, loan documentation, and international insolvency are handled clearly and concisely. In his discussion of credit decisions and credit controls, for example, Donaldson describes thoroughly the various ways in which banks organize to approve credit, to analyze new and existing borrowers, and to monitor loans once they have been approved. He also traces the development of international lending-bank failures and defaults on international loans-from the early nineteenth century to the present.
"A Halsted Press book."
Includes bibliography, index.
rpm 30/04/2018
Loans
Keywords: Loans, Foreign; Bank loans; International lending; Commercial banks